Delivering Integrated Eye Care through Social Franchising Model: An Implementation Science Study in Rural China...24th International Conference on Integrated Care, April 22-24, 2024, Belfast, Ireland - Xiaodong Dong; Xiaochen Ma (International Journal of Integrated Care (IJIC))
Background: Integration of services is hampered by the fragmented supply of health and social services as a result of specialization, differentiation, segmentation and decentralization. Fragmentation results in suboptimal care, higher cost due to duplication and poor quality of care. This necessitates the imperative for integration at both organizational and services levels. In low- and middle-income countries, there is a growing interest in organizational integrations that enhance access and quality of healthcare services while being scalable and financially sustainable. The implementation process of these integrated care models needs thorough exploration to understand their penetration and sustainability. This study utilizes the updated Consolidated Framework for Implementation Research (CFIR 2.0) to assess the implementation performance of Smart Focus, a social franchising model delivering integrated eye care for children in rural China within designated counties. We aim to examine key barriers and facilitators influencing the implementation outcomes, with a focus on the integrated eye care aspect. Methods: Employing a mixed-methods approach, we retrospectively evaluate the Smart Focus implementation using CFIR 2.0. Quantitative analysis centers on penetration and sustainability measures derived from historical administrative data, specifically focusing on integrated eye care delivery. Qualitative analysis includes semi-structured interviews and focus group discussions with key decision-makers and innovation deliverers, exploring the determinants influencing implementation performance. Two researchers independently code the data, and subsequent content analysis follows pre-defined CFIR 2.0 constructs. Results: Smart Focus, through local Med-Eds integration, successfully established vision centers in 23 national designated poverty counties, conducting over 350,000 screenings and distributing 72,000 pairs of eyeglasses since 2015. Despite these achievements, long-term sustainability poses a challenge. Twenty constructs emerged from informants' responses as influential factors in implementation of the integrated eye care delivery. Facilitators include the strength and quality of evidence, high trialability and adaptability, relative advantages, standardized available resources and infrastructure, and training activities. Barriers encompass the complexity of cross-departmental cooperation, underestimated variable costs, peer competition, insufficient incentives, employee turnover due to a lack of commercial capabilities, and the absence of feedback and readjustment activities for integrating the innovation into the dynamic context. Conclusion: Through CFIR 2.0, we evaluate the implementation of a social franchising model for integrated eye care for children in rural China. This study provides a relevant framework for expanding sustainable, quality eye care coverage with an emphasis on the integrated eye care components. We underscore the challenges in balancing social and business objectives within such models, crucial for effective implementation. Addressing these complexities is imperative for advancing social franchising in low- and middle-income countries, thereby contributing to the evolution of the CFIR framework and to pattern innovation and promotion to facilitate the integrated eye care services.